VARIASI KARAKTERISTIK PERTUMBUHAN TACCA LEONTOPETALOIDES (L) KUNTZE (TACCACEAE) DI PULAU JAWA DAN PULAU-PULAU KECIL SEKITARNYA - Syarif, Fauzia; Lestari, Peni; Wawo, Albert Husein (BERITA BIOLOGI, 2014)
An increasing of population, land conversion, and the behaviour changes in many crops due to global warming could produce a significant negative effect to food security in many countries, including Indonesia. In order to maintain the availability of food, we should find out alternative foods based on corp comodities that can adapt to future agricultural land conditions. One species to be promoted for that purpose is Tacca leontopetaloides (taka). This study was aimed to determine growth characteristics variations of taka in Java and its surrounding small islands through exploration and interview methods. Results indicated that there were two morphological variations of taka based on the canopy colour, namely green and purple. Taka found growing in coastal areas up to100 m above sea level. The light intensity and soil type greatly affected their growth. These plants lived either solitary or in a groups, grow well on sandy soil to clay, under the shade and open areas. Species around taka allegedly contributed in determining taka growth and production. Taka tuber can be an alternative carbohydrate source for supporting food self-sufficiency in coastal communities.